The Effect of Bank Competition on the Bank's Incentive to Collateralize - Christa Hainz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2007)
It has been argued that competing banks make inefficiently frequent use of collateralization in situations where they are better able to evaluate a project's risk than entrepreneurs. We study the bank's choice between screening and collateralization in a model where banks do not have this superior screening skill. In particular, we study the effect of bank competition on this choice. We find that competing banks use collateral less often than a monopolistic bank because competition will intensify if both banks collateralize. Moreover, bank competition is welfare improving if collateralization is rather costly.
urn:nbn:de:bvb:19-epub-13336-5
Keywords: D82; G21; K00; 330; collateralization; screening; incentives; bank competition